Ultrasound Imaging Current Topics - Okechukwu Erondu, Felix (IntechOpen, 2022)
Ultrasound Imaging - Current Topics presents complex and current topics in ultrasound imaging in a simplified format. It is easy to read and exemplifies the range of experiences of each contributing author. Chapters address such topics as anatomy and dimensional variations, pediatric gastrointestinal emergencies, musculoskeletal and nerve imaging as well as molecular sonography. The book is a useful resource for researchers, students, clinicians, and sonographers looking for additional information on ultrasound imaging beyond the basics.